Mutational analysis of driver genes defines the colorectal adenoma: in situ carcinoma transition - Jungwirth, Jiri; Urbanova, Marketa; Boot, Arnoud; Hosek, Petr; Bendova, Petra; Siskova, Anna; Svec, Jiri; Kment, Milan; Tumova, Daniela; Summerova, Sandra; Benes, Zdenek; Buchler, Tomas; et al. (Scientific reports, 2022)
A large proportion of colorectal carcinomas (CRC) evolve from colorectal adenomas. However, not all individuals with colonic adenomas have a risk of CRC substantially higher than those of the general population. The aim of the study was to determine the differences or similarities of mutation profile among low- and high-grade adenomas and in situ carcinoma with detailed follow up. We have investigated the mutation spectrum of well-known genes involved in CRC (such as APC, BRAF, EGFR, NRAS, KRAS, PIK3CA, POLE, POLD1, SMAD4, PTEN, and TP53) in a large, well-defined series of 96 adenomas and in situ carcinomas using a high-throughput genotyping technique. Besides, the microsatellite instability and APC and MLH1 promoter methylation were studied as well. We observed a high frequency of pathogenic variants in the studied genes. The APC, KRAS and TP53 mutation frequencies were slightly lower in adenoma samples than in in situ carcinoma samples. Further, when we stratified mutation frequency based on the grade, the frequency distribution was as follows: low-grade adenoma-high-grade adenomas-in situ carcinoma: APC gene 42.9-56.0-54.5%; KRAS gene 32.7-32.0-45.5%; TP53 gene 8.2-20.0-18.2%. The occurrence of KRAS mutation was associated with the presence of villous histology and methylation of the APC promoter was significantly associated with the presence of POLE genetic variations. However, no association was noticed with the presence of any singular mutation and occurrence of subsequent adenoma or CRC. Our data supports the multistep model of gradual accumulation of mutations, especially in the driver genes, such as APC, TP53 and KRAS.
Keywords: mutace; Adenoma; kolorektální nádory; Female; mikrosatelitní nestabilita; ženské pohlaví; Colorectal Neoplasms; adenom; lidé; Mutation; následné studie; metylace DNA; Microsatellite Instability; Carcinoma in Situ; prognóza; Follow-Up Studies; Male; nádorové biomarkery; Aged; DNA Methylation; Prognosis; Biomarkers, Tumor; senioři; mužské pohlaví; karcinom in situ; Humans